The Affordable Care Act and the market for higher education - Rajashri Chakrabarti; Maxim Pinkovskiy (Federal Reserve Bank of New York, 2018)
Through changing the connection between insurance and employment, the Affordable Care Act (ACA) has affected people's incentives to obtain education. We employ a triple-difference strategy comparing counties with different levels of uninsurance pre-ACA and in states with different Medicaid expansion decisions across time to investigate changes in enrollment in different types of higher education institutions. We find that enrollment in less-than-two-year for-profit colleges increased more between high- and low-uninsurance counties in states that expanded Medicaid relative to states that didn't, with nearly all the increase taking place after the 2012 Supreme Court decision that gave states the right to choose not to expand Medicaid. Differential enrollment is flat for all other comparable college types. We find this differential increase in less-than-two-year for-profit college enrollment to be remarkably general across demographic characteristics, and robust to controlling for confounders such as the differential impact of the Great Recession.
Keywords: H4; I1; I2; 330; affordable care act; postsecondary education; for-profit schools; health insurance; Medicaid